Childfree dan Hukum Menggunakan Alat Kontrasepsi dalam Perspektif Fikih Kontemporer : Childfree and the Law of Using Contraception in a Contemporary Fiqh Perspective) - Syari'ah, Atiris; Tutik Hamidah (ISTIDLAL, 2024)
Childfree or consciously deciding not to have children and trying to prevent pregnancy with contraception are still a hot topic of debate among Indonesian society. In this paper, the author attempts to elaborate on childfree and contraception from various perspectives, with an emphasis on contemporary jurisprudential viewpoints. This research employs a qualitative approach, utilizing a literature study methodology. To obtain representative data, the researchers collected information from various literary sources and analyzed it using descriptive techniques, resulting in the conclusion that, in general, there is no text that declares it forbidden for individuals to choose a childfree lifestyle or contraception. However, in some cases and perspectives, it can be discouraged (makruh) or even forbidden (haram) if there are reasons beyond the objectives of Islamic law (maqashid al-syari’ah).